KONSEP, BATASAN, DAN JALUR PENDIDIKAN ISLAM DALAM PERSPEKTIF AL-QUR’AN DAN HADIS - Sari Ramadani Basa; Defni Bukhari; Ansori Ansori; Iwan Aprianto (TEACHER : Jurnal Inovasi Karya Ilmiah Guru, 2026)
ABSTRACT Islamic education carries a strategic role in shaping individuals who are faithful, knowledgeable, and morally upright. Yet, the currents of modernization, secularization, and digital disruption have pushed its meaning toward mere ritual instruction, often sidelining its function in character formation and the integration of knowledge and practice. This problem underlines the need for a comprehensive study that fully integrates three dimensions commonly discussed separately: the concept, scope, and pathways of Islamic education, so that understanding of it remains holistic rather than partial. This study aims to describe the concept of Islamic education encompassing tarbiyah, ta’lim, and ta’dib; to explain the scope of Islamic education in terms of its domain, principles, and characteristics; and to identify its pathways from both classical and contemporary international perspectives. A qualitative library research method was employed, examining Qur’anic verses, Prophetic hadith, and national and international scholarly literature thematically, analyzed through content analysis. The findings indicate that the concept of Islamic education originates from the Qur’an, hadith, and ijtihad, with the primary goal of forming insan kamil (the perfect human being); the scope of Islamic education covers aqidah, worship, and morality grounded in tawhid, the integration of knowledge and practice, and physical-spiritual balance; and the pathways of Islamic education consist of formal education (madrasah, pesantren, Islamic higher education), non-formal education (majelis taklim, religious courses), and informal education (family education), all of which are complementary. The study concludes that synergy among these pathways is key to the success of Islamic education in confronting modernization and digitalization without losing its Islamic identity, while also enriching the discourse of Islamic education within a global context. ABSTRAK Pendidikan Islam memiliki peran penting dalam membentuk manusia yang beriman, berilmu, dan berakhlak, namun kajian mengenai konsep, batasan, dan jalur pendidikan Islam masih banyak dibahas secara parsial sehingga belum menunjukkan keterkaitan antarketiganya dalam satu kerangka yang utuh. Penelitian ini bertujuan mendeskripsikan konsep pendidikan Islam, menjelaskan batasannya, serta mengidentifikasi jalur pendidikan Islam berdasarkan Al-Qur'an, Hadis, dan perkembangan diskursus pendidikan Islam kontemporer. Penelitian menggunakan pendekatan kualitatif dengan metode library research. Data diperoleh dari ayat-ayat Al-Qur'an, hadis, serta literatur ilmiah nasional dan internasional yang relevan, kemudian dianalisis menggunakan teknik content analysis melalui pengodean, kategorisasi, dan sintesis tematik. Hasil penelitian menunjukkan bahwa konsep pendidikan Islam dibangun melalui keterpaduan tarbiyah, ta'lim, dan ta'dib yang mengarah pada pembentukan insan kamil. Batasan pendidikan Islam mencakup ruang lingkup akidah, ibadah, dan akhlak yang diselenggarakan berdasarkan prinsip tauhid, integrasi ilmu dan amal, keseimbangan jasmani dan rohani, serta nilai-nilai ilahiyah. Implementasi pendidikan Islam berlangsung melalui jalur formal, nonformal, dan informal yang saling melengkapi. Penelitian ini menyimpulkan bahwa konsep, batasan, dan jalur pendidikan Islam membentuk kerangka integratif yang dapat menjadi landasan konseptual bagi pengembangan kajian maupun praktik pendidikan Islam.